2007
DOI: 10.1111/j.1440-1746.2007.05068.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost‐effectiveness of antiviral therapies in patients with chronic hepatitis B: A systematic review of economic evidence

Abstract: Background and Aim: Economic efficiency of the alternative antiviral therapies for chronic hepatitis B has not been systematically investigated and their quality remains unknown. The aim of the present study was to systematically overview economic evidence of antiviral therapies for chronic hepatitis B. Methods: We searched six databases and eight major journals supplemented with screening references of eligible studies. Full economic evaluations comparing alternative antiviral therapies in patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
(77 reference statements)
0
21
2
Order By: Relevance
“…A systematic review of cost-effectiveness of antiviral therapies (Sun and colleagues 48 ) described studies published from 2000 to 2007, including three studies described here (Kanwal and colleagues 38 , Buti and colleagues 47 and Sullivan and colleagues 45 ) and some of the studies identified in our previous review. 12 Sun and colleagues 48 also reviewed other cost studies based on randomised, non-randomised and retrospective cohort data that did not meet the inclusion criteria of the present or previous reviews and were generally assessed by Sun and colleagues 48 as being of moderate or poor quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of cost-effectiveness of antiviral therapies (Sun and colleagues 48 ) described studies published from 2000 to 2007, including three studies described here (Kanwal and colleagues 38 , Buti and colleagues 47 and Sullivan and colleagues 45 ) and some of the studies identified in our previous review. 12 Sun and colleagues 48 also reviewed other cost studies based on randomised, non-randomised and retrospective cohort data that did not meet the inclusion criteria of the present or previous reviews and were generally assessed by Sun and colleagues 48 as being of moderate or poor quality.…”
mentioning
confidence: 99%
“…Four fully published economic evaluations met the inclusion criteria and were included. [44][45][46][47] In addition, one systematic review of economic evidence of cost-effectiveness of antiviral therapies in CHB patients (Sun and colleagues 48 ) was included.…”
mentioning
confidence: 99%
“…However, they show methodological differences (the drugs being compared, the timeframe, perspective, modelling) and heterogeneity of the simulated population. 25 Costa et al undertook a study with a ten-year-timeframe comparing entecavir with lamivudine in HBeAg positive and negative patients. 7 Those who developed resistance to lamivudine had adefovir added to their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a common unit to allow comparisons between different disease groups or intervention programmes (Weinstein, Torrance, & McGuire, 2009). This method is particularly useful in the analysis of preventive health programmes, such as anti-viral treatment in CHB patients (Kanwal et al, 2005;Sullivan et al, 2007;Sun et al, 2007;Yuan et al, 2008).…”
Section: Preference-based Measure (Utility) Of Hrqolmentioning
confidence: 99%
“…Cost-effectiveness analysis (CEA) is an area of increasing interest among researchers, physicians and policy makers (Sun et al, 2007). CEA is a method of summarizing the health benefits and resources used by health programmes, therefore policy makers can select among them (Russell, Gold, Siegel, Daniels, & Weinstein, 1996;Weinstein, 1990;Weinstein, Siegel, Gold, Kamlet, & Russell, 1996).…”
Section: Preference-based Measure (Utility) Of Hrqolmentioning
confidence: 99%